Desenvolvimento de um equipamento automatizado com luz UV para desinfecção de carros de transporte de dietas do Setor de Nutrição em um Hospital Universitário Brasileiro - Gomes, Adriana Barros Luna (2025)
Introduction: The presence of pathogenic microorganisms in hospital environments poses a constant challenge for the control of healthcare-associated infections (HAIs), especially due to the vulnerability of patients. Among the factors contributing to the spread of these agents is the inadequate cleaning of food transport carts, which may act as indirect vectors of contamination. In this context, the development of effective technological solutions for surface disinfection is essential. Objective: To develop a UV-C light-based device for the disinfection of hospital dietary transport carts, from industrial design to prototype construction. Methodology: This is an applied research project focused on technological development and health innovation, aiming to evaluate and improve strategies for hospital disinfection. The study was divided into three stages: (1) literature review, (2) prior art search, and (3) development of the industrial design and construction of the prototype. The literature review was conducted using databases such as SciELO, LILACS, CAPES, BIREME, PubMed, and Scopus, in addition to technical literature. The prior art search included patent databases such as ESPACENET, PATENTSCOPE, INPI, and ORBIT. Results: A significant association was found between the cleaning method/condition and the microbial contamination levels of the dietary transport carts. Carts cleaned only with 70% alcohol (Group 3) showed a lower average contamination (45 CFU) and a lower likelihood of contamination compared to those cleaned with detergent + ethanol (Group 1). Carts without sanitation (Group 2) had the highest average contamination (240 CFU). Carts disinfected with UV-C light (Group 4) showed no microbial growth, demonstrating superior efficacy. Conclusions: The UV-C light disinfection device prototype was successfully developed, and an invention disclosure (NIA687 – 2025) was submitted to the Technology Innovation Office. The proposed equipment offers an automated, effective, and functional solution for disinfecting hospital dietary transport carts. Future steps include long- term microbiological safety validation, cost-benefit analysis, and usability evaluation by healthcare professionals, aiming to ensure its effectiveness and applicability in clinical practice.